The Psychological Frustration Resistance of Students with Sports Advantages in English Learning - Chunyan Peng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
To investigate the psychological resilience of students in the context of English learning, this research advocates for an examination of the psychological resilience among students who possess athletic advantages. The participants recruited for this study consist of third, fourth, and fifth-grade students enrolled at the primary school designated as the first experimental institution within a specific city. These participants exhibit normative levels of intelligence and lack any sensory impairments that could potentially hinder English language acquisition, thereby excluding factors of physical origin influencing English learning outcomes. Their psychological attributes are examined in detail. Based on their performance in the three mid-term and final examinations during the 2020-2021 academic year, students who consistently ranked below the 30th percentile of the entire grade across all three assessments are classified as belonging to the "learning disabilities group" in English language acquisition. Similarly, students who consistently ranked within the top 30% across the same assessments are identified as proficient English learners and form the "academic excellence group," serving as the comparison group. The assessment of emotional aptitude primarily revolves around two dimensions: English learning anxiety and resilience. This evaluation utilizes the "Elementary School Field Academic Emotion Questionnaire" and the "Resilience Scale." The latter comprises 26 items, with an internal consistency score of 0.866 and a standardized mean (x̄) of 0.872, indicating robust reliability for application within this cohort. Students with English learning disabilities exhibit markedly lower cognitive and emotional abilities compared to academically proficient peers. Variances in cognitive and emotional abilities exist across different grade levels, as well as among students of different genders. The cognitive and emotional deficiencies observed in students with English learning disabilities are significantly associated with their learning challenges, indicating a reciprocal influence between cognitive and emotional abilities. Enhancing students' resilience can facilitate their adept navigation of challenges encountered in English learning, fostering heightened enthusiasm, a positive mindset, and enhanced efficacy in the English teaching process. Furthermore, students with athletic advantages may demonstrate elevated psychological resilience, enabling them to confront challenges and setbacks more effectively in the context of English learning. This, in turn, augments motivation, perseverance, and ultimately contributes to enhanced language proficiency.